FAKTOR-FAKTOR YANG MEMENGARUHI MAHASISWA DALAM MENGGUNAKAN OJEK ONLINE - DESKA, DELVI AMY; JAYANEGARA, KETUT; NILAKUSMAWATI, DESAK PUTU EKA (E-Jurnal Matematika; Vol 12 No 3 (2023)DO - 10.24843/MTK.2023.v12.i03.p418, 2023)
Transportation is a very important field of activities in the life of Indonesian people. Recognizing the importance  role of transportation, traffic and road transportation must be organized in an integrated national transportation system and able to realize the availability of transportation services in accordance to the level of need. One of the most widely used transportation is ojek online. Of course, some factors become the influence of the use of online motorcycle taxis. One quantitative method that can measure customer perception using online motorcycle taxis is the Factor Analysis method, which is a statistical analysis used to find out the factors that underlie and show interrelationships between changemakers. Based on questionnaires distributed to 150 students in the FMIPA environment of Udayana University in 2021 and after an analysis of factors on questionnaire data, it was obtained that factors which influence students' decisions to use online motorcycle taxis are location and destination factors, service factors, application factors, and promotional factors. These factors can explain the diversity of students to use online motorcycle taxis by 34.666%; 28,897%; 22.563% and 10.873%. The dominant factor that mostly influence students' decision to use online motorcycle taxis is the factor of place and destination location that can be explained by 34.666%.